-21p-15-4+40p=27-18p

Simple and best practice solution for -21p-15-4+40p=27-18p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -21p-15-4+40p=27-18p equation:


Simplifying
-21p + -15 + -4 + 40p = 27 + -18p

Reorder the terms:
-15 + -4 + -21p + 40p = 27 + -18p

Combine like terms: -15 + -4 = -19
-19 + -21p + 40p = 27 + -18p

Combine like terms: -21p + 40p = 19p
-19 + 19p = 27 + -18p

Solving
-19 + 19p = 27 + -18p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '18p' to each side of the equation.
-19 + 19p + 18p = 27 + -18p + 18p

Combine like terms: 19p + 18p = 37p
-19 + 37p = 27 + -18p + 18p

Combine like terms: -18p + 18p = 0
-19 + 37p = 27 + 0
-19 + 37p = 27

Add '19' to each side of the equation.
-19 + 19 + 37p = 27 + 19

Combine like terms: -19 + 19 = 0
0 + 37p = 27 + 19
37p = 27 + 19

Combine like terms: 27 + 19 = 46
37p = 46

Divide each side by '37'.
p = 1.243243243

Simplifying
p = 1.243243243

See similar equations:

| 4x^2+12x-15=5 | | u^2+4u-23=0 | | x^2+xy=24 | | 6.84*x=3 | | f(x)=x^3-4x+4 | | 2cos^2-1=0 | | x*2+2x=16 | | u^2+6u=47 | | X^2+7=7X+3 | | 1.2q-1.9-1.3q=-1.1q-3.6 | | u^2-4u=25 | | -3.7u=7.75 | | A=2x^2+15x+18 | | -3x^2-24x+17=-40 | | -5x^2-20x+35=30 | | 2x^2-14x+10=26 | | y=-x+30 | | -8(4-x)+2x+12=30 | | log[2](x-5)-log[2](x+2)=3 | | f(x)=6x^2+x-15 | | -5x^2-20x+35=0 | | 56x+23y= | | 7a-9=-2a+4 | | 5(-5+p)=75 | | -3x^2-24x+17=0 | | 4(x-2)+3x+5=11 | | y^2+20y-41=0 | | 2+10=8 | | 12y^2+24y=5 | | p=9+6ln(4x+1) | | x+5*5=3x*2 | | p^2-26p=41 |

Equations solver categories